The influence of the end-group on the chiral self-assembly of all-conjugated block copolymers. Issue 37 (10th August 2017) - Van Den Eede, M.-P.; Bedi, A.; Delabie, J.; De Winter, J.; Gerbaux, P.; Koeckelberghs, G.
Abstract : This research demonstrates the influence of the end-group on the self-assembly of conjugated polymers. Abstract : The self-assembly of all-conjugated block copolymers is an effective way to obtain well-ordered structures at the nanoscale. Although these polymers possess an end-group and a lot of research has been done on their self-assembly, the influence of the end-groups has hardly been considered. Both the nature of the blocks as well as the degree of polymerization (DP) play a crucial role in the solubility of the different blocks in a conjugated block copolymer. Here, we hypothesize that also the end-group is of importance: bulkier end-groups increase the solubility of that particular preceding block and thus will have an influence on the self-assembly. This hypothesis is validated using three series of all-conjugated block copolymers in which the blocks are composed of the two enantiomers of a chiral monomer.